Dampak Stunting Terhadap Keterlambatan Kemampuan Bicara Anak di Kendari, Sulawesi Tenggara - Yusuf, Sulfianti A; Kurniawan, Fajar; Majid, Ruslan (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2025)
Stunting is a growth failure condition caused by chronic malnutrition during the first 1,000 days of life, which not only affects a child’s height but also has serious consequences on cognitive development, including speech delays. In Indonesia, including Kendari City, this issue remains a significant challenge despite a decline in its prevalence to 24.4% in 2021. This study employed a quantitative approach with an explanatory design, conducted from May to July 2024 in Kendari, involving 105 parents of toddlers selected through purposive sampling. Data were collected using questionnaires and analyzed using Partial Least Squares (PLS) version 3. Method identified that the main causes of stunting include lack of maternal nutritional intake during pregnancy, suboptimal breastfeeding, and inadequate sanitation conditions. Stunting status was found to be closely related to speech delays, which were exacerbated by a lack of verbal stimulation in the family and the presence of hearing loss that was not immediately recognized. Although most parents understand the importance of nutrition and nurturing, the application in daily life is still not optimal. The conclusion of this study shows that stunting has a contribution to speech delay in children, so comprehensive intervention efforts are needed at the community level, including improving nutrition education, access to health services, improving sanitation, and creating an environment that supports the stimulation of child development through cooperation between the government, health workers, and the community.